Synthesis of Fe-impregnated biochar from food waste for Selenium(Ⅵ) removal from aqueous solution through adsorption: Process optimization and assessment - Hong, Seung Hee; Lyonga, Fritz Ndumbe; Kang, Jin Kyu; Seo, Eun Jin; Lee, Chang Gu; Jeong, Sanghyun; Hong, Seong Gu; Park, Seong Jik (Chemosphere, 2020)
Iron-impregnated food waste biochar (Fe-FWB) was synthesized for Se(Ⅵ) removal from aqueous solution. The effect and interactive effects of different parameters including pyrolysis time, temperature, and Fe concentration were explored using response surface methodology (RSM) to enhance conditions to achieve the highest Se(Ⅵ) removal using Fe-FWB. Pyrolysis time was not significant for Se(Ⅵ) adsorption capacity of Fe-FWB, but temperature and Fe concentration were found to be significant. The highest adsorption was achieved at 3.47 h and 495.0 °C with an Fe concentration of 0.44 M. Fe-FWB synthesized under optimum conditions were used to investigate the kinetic, equilibrium, and thermodynamic adsorption of Se(Ⅵ). Se(Ⅵ) adsorption reached equilibrium within 6 h, and both pseudo-second order and pseudo-first order models were suitable for describing kinetic Se(Ⅵ) adsorption. The Freundlich model was found to suitably fit the equilibrium adsorption data than the Langmuir model. The highest adsorption capacity of Fe-FWB for Se(Ⅵ) was 11.7 mg g−1. Se(Ⅵ) adsorption on Fe-FWB was endothermic and spontaneous. The enthalpy change for Se(Ⅵ) adsorption was 54.4 kJ mol−1, and the entropy change was negative at 15–35 °C. The increment of solution pH from 3 to 11 decreased the Se(Ⅵ) adsorption from 19.2 to 7.4 mg g−1. The impact of interfering anions on Se(Ⅵ) adsorption followed the lineup: HCO3− > HPO42− > SO42− > NO3−. When compared to some adsorbents, the adsorption capacity of Se(Ⅵ) onto Fe-FWB was comparable even at neutral pH and the Fe-FWB was granular. These results indicate that Fe-FWB has prospective application in the removal of Se(Ⅵ) from aqueous solutions.
Keywords: Adsorption capacities; Bio chars; Equilibrium adsorption; Optimum conditions; Prospective applications; Pseudo second order; Response surface methodology; Thermodynamic adsorption; Adsorption; Anions; Charcoal; Food; Hydrogen-Ion Concentration; Iron; Kinetics; Prospective Studies; Selenium; Temperature; Thermodynamics; Water; Water Pollutants, Chemical; Biochar; Food waste; Impregnation; Iron; Selenium; Temperature